Determination of molecular mechanisms of cellular plasticity and pancreas tissue remodeling under conditions of experimental diabetes - Ivanenko, T.; Аbramov, A. (Journal of Education, Health and Sport, 2026)
The pancreas functions as a highly integrated system , in which endocrine islets closely interact with exocrine tissue and vascular-stromal-immune microenvironment. Under conditions of experimental diabetes, chronic hyperglycemia, dyslipidemia, oxidative-inflammatory signals and impaired proteostasis initiate prolonged tissue remodeling, the central mechanism of which is cellular plasticity, namely the restructuring of transcriptional-epigenetic programs and secretory competence of endocrine cells. Identification of key molecular nodes of this response using a panel analysis of expression (2⁻ΔΔCt) is necessary to distinguish adaptive and maladaptive remodeling scenarios and to substantiate potential targets for the correction of diabetes-associated disfunction. The aim of the work: to determine the molecular mechanisms of cellular plasticity and remodeling of the pancreas under conditions of experimental diabetes mellitus by analyzing the expression profile of key genes. Materials and methods. For the analysis of gene expression, the real-time reverse transcription polymerase chain reaction method was used using the PARN-405Z RT² Profiler™ PCR Array Rat Stem Cell kit (QIAGEN, Germany), where the pancreas was the object of the study in experimental animals. Results. In the pancreas of rats under conditions of experimental diabetes mellitus, an increase in the expression of 7 genes (Aldh1a1, Bmp1, Btrc, Cd8a, Cdc42, Dtx2, Myc) was detected relative to the control using the 2⁻ΔΔCt method. The most pronounced was the increase in Cdc42 (11.49 times). Also an increase in Bmp1 (7.13), Myc (5.21), Btrc (5.16), Dtx2 (3.19), Aldh1a1 (2.94), and Cd8a (2.24) fold noted was, reflecting a combination of cytoskeletal-secretory adaptation, matrix remodeling, rearrangement of ubiquitin-dependent and Notch-context signaling and a possible immune contribution. Conclusions: 1. In the pancreas of rats under conditions of experimental diabetes, a limited but distinct profile of increased gene expression (Aldh1a1, Bmp1, Btrc, Cd8a, Cdc42, Dtx2, Myc) was detected by the 2⁻ΔΔCt method, reflecting a holistic tissue response to chronic metabolic stress. 2. The dominant increase in Cdc42 (+11.49) is consistent with the predominant activation of the cytoskeletal-secretory module and can be interpreted as a compensatory reconfiguration of regulated exocytosis of endocrinocytes in a diabetes-associated stress context. 3. The increase in Bmp1 (+7.13) together with the increase in Btrc (+5.16) and Dtx2 (+3.19) indicates the involvement of stromal-matrix remodeling and ubiquitin-dependent and signaling rearrangements that shape the islet microenvironment and modify plasticity trajectories. 4. The combination of increases in Cd8a (+2.24), Aldh1a1 (+2.94) and Myc (+5.21) highlights the contribution of immune-stress and detoxification-adaptive programs in unfractionated tissue, which requires further cell-specific validation to clarify the source of the signals and their functional consequences.